Implementation of Community Empowerment Model for Accelerating Stunting Reduction In Indonesia - Heni Hastuti; Endang Sutisna Sulaeman; Anak Agung Alit Kirti Estuti Narendra Putri; Amalia Khurotul Mahzunah (Journal of Health Promotion and Behavior, 2026)
Background: According to the World Health Organization (WHO), Indonesia ranks the third highest prevalence of stunting in Asia. In response to this condition, WHO has set a target to reduce stunting by 40%. This study aims to formulate an implementative community empowerment model consisting of 1) input, including information, motivation, behavioral skills, and community organization and development; 2) process, comprising the empowerment process; and 3) output, namely behavioral performance for accelerating stunting reduction in Indonesia. In addition, this study seeks to identify the factors influencing community empowerment in stunting prevention and to analyze the relationship between empowerment components and behavioral performance in accelerating stunting reduction efforts. Subjects and Method: A concurrent mixed-methods design integrating quantitative and qualitative approaches was employed. The study was conducted in Karanganyar Regency, Central Java, Indonesia, from June to August 2023. The quantitative component used quota sampling, with 15 samples per exogenous variable, resulting in 225 members of the Stunting Reduction Acceleration Team. Data were collected through structured questionnaires and analyzed using path analysis. The qualitative component involved 24 purposively selected informants. Data were collected through in-depth interviews and analyzed using content analysis. Results: Information-motivation-behavioral skills and community organization and development significantly influenced the empowerment process (OR=5.11; 95% CI=2.46 to 10.61; p<0.001 and OR= 13.04; 95% CI=6.30 to 27.01; p<0.001, respectively). Community organization and development significantly improved stunting prevention performance (OR=3.64; 95% CI=1.62 to 8.16; p=0.002), whereas information-motivation-behavioral skills showed a protective effect (OR=0.43; 95% CI=0.21 to 0.88; p=0.021). The empowerment process was not significantly associated with performance (OR=1.12; 95% CI=0.50 to 2.52; p=0.770). Conclusion: Community organization and development are important determinants of behavioral performance in stunting prevention and contribute to accelerating stunting reduction efforts.